Obinutuzumab Effectively Depletes Key B-cell Subsets in Blood and Tissue in End-stage Renal Disease Patients. Issue 2 (19th January 2023) - Looney, Cary M.; Schroeder, Aaron; Tavares, Erica; Garg, Jay; Schindler, Thomas; Vincenti, Flavio; Redfield, Robert R.; Jordan, Stanley C.; Busque, Stephan; Woodle, E. Steve; Khan, Jared; Eastham, Jeffrey; et al.
Abstract : Background: The THEORY study evaluated the effects of single and multiple doses of obinutuzumab, a type 2 anti-CD20 antibody that induces antibody-dependent cell-mediated cytotoxicity and direct cell death, in combination with standard of care in patients with end-stage renal disease. Methods: We measured B-cell subsets and protein biomarkers of B-cell activity in peripheral blood before and after obinutuzumab administration in THEORY patients, and B-cell subsets in lymph nodes in THEORY patients and an untreated comparator cohort. Results: Obinutuzumab treatment resulted in a rapid loss of B-cell subsets (including naive B, memory B, double-negative, immunoglobulin D + transitional cells, and plasmablasts/plasma cells) in peripheral blood and tissue. This loss of B cells was associated with increased B cell–activating factor and decreased CXCL13 levels in circulation. Conclusions: Our data further characterize the mechanistic profile of obinutuzumab and suggest that it may elicit greater efficacy in indications such as lupus where B-cell targeting therapeutics are limited by the resistance of pathogenic tissue B cells to depletion.